Applying Sticky and Violation Shutdown Mode on Security Port Switch for Security Wan Infrastructure Network - Ritonga, Ikhsan; Ilham Faisal; Tengku Mohd.Diansyah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Network security is a crucial aspect of managing information technology infrastructure. The risk of network threats, such as data theft and operational disruptions, increases as access points proliferate. One technique to mitigate these risks is port security. This study aims to implement and evaluate the effectiveness of switch port security in enhancing security within a Wide Area Network (WAN) infrastructure. The port security feature is configured using sticky mode and violation shutdown, allowing the recognition and authorization of legitimate devices based on their Media Access Control (MAC) addresses. A simulation using Cisco Packet Tracer was conducted to test this approach, where port security was applied to prevent unauthorized access. The results show that switch port security with sticky mode and violation shutdown effectively identifies and blocks unauthorized devices. When a device with an unknown MAC address attempts to access the network, the switch automatically disables the corresponding port, ensuring that only authorized devices can connect. The process of recovering disabled ports also proved to be quick and straightforward for network administrators. In conclusion, the implementation of switch port security in WAN infrastructure significantly strengthens network security, protects data from unauthorized access, and ensures optimal network availability and performance.